(untitled) (International journal of medical sciences, 2025)
Infectious diseases remain one of the leading causes of global morbidity and mortality, affecting populations across all regions. The effective management of these conditions relies on two key pillars: treatment and prevention. Treatment involves timely diagnosis, appropriate antimicrobial therapy, supportive care, and management of complications. The selection of antibiotics, antivirals, antifungals, or antiparasitic drugs depends on the causative agent, disease severity, and patient comorbidities. In recent years, antimicrobial resistance has emerged as a major global health threat, highlighting the need for rational prescribing and stewardship programs. Preventive measures are equally essential in controlling infectious diseases, reducing disease burden, and avoiding outbreaks. Strategies include vaccination, improved sanitation, vector control, health education, and adherence to infection control protocols in healthcare settings. Preventive approaches not only reduce transmission but also minimize healthcare costs and improve population health. The COVID-19 pandemic has demonstrated the importance of integrating both treatment and prevention into public health strategies. This article reviews the principles of infectious disease management, emphasizing the complementary role of preventive measures. A multidisciplinary, evidence-based approach combining treatment and prevention is crucial to reducing the global burden of infectious diseases and safeguarding future generations.